Prehospital end-tidal carbon dioxide is predictive of death and massive transfusion in injured patients: An Eastern Association for Surgery of Trauma multicenter trial. Issue 2 (22nd February 2022) - Campion, Eric M.; Cralley, Alexis; Sauaia, Angela; Buchheit, Ron C.; Brown, Austin T.; Spalding, M. Chance; LaRiccia, Aimee; Moore, Scott; Tann, Kimberly; Leskovan, John; Camazine, Maraya; Barnes, Stephen L.; et al.
Abstract : BACKGROUND: Prehospital identification of the injured patient likely to require emergent care remains a challenge. End-tidal carbon dioxide (ETCO2) has been used in the prehospital setting to monitor respiratory physiology and confirmation of endotracheal tube placement. Low levels of ETCO2 have been demonstrated to correlate with injury severity and mortality in a number of in-hospital studies. We hypothesized that prehospital ETCO2 values would be predictive of mortality and need for massive transfusion (MT) in intubated patients. METHODS: This was a retrospective multicenter trial with 24 participating centers. Prehospital, emergency department, and hospital values were collected. Receiver operating characteristic curves were created and compared. Massive transfusion defined as >10 U of blood in 6 hours or death in 6 hours with at least 1 U of blood transfused. RESULTS: A total of 1, 324 patients were enrolled. ETCO2 (area under the receiver operating characteristic curve [AUROC], 0.67; confidence interval [CI], 0.63–0.71) was better in predicting mortality than shock index (SI) (AUROC, 0.55; CI, 0.50–0.60) and systolic blood pressure (SBP) (AUROC, 0.58; CI, 0.53–0.62) (p < 0.0005). Prehospital lowest ETCO2 (AUROC, 0.69; CI, 0.64–0.75), SBP (AUROC, 0.75; CI, 0.70–0.81), and SI (AUROC, 0.74; CI, 0.68–0.79) were all predictive of MT. Analysis of patients with normotension demonstrated lowest prehospital ETCO2 (AUROC, 0.66; CI, 0.61–0.71), which was more predictive of mortality than SBP (AUROC, 0.52; CI, 0.47–0.58) or SI (AUROC, 0.56; CI, 0.50–0.62) (p < 0.001). Lowest prehospital ETCO2 (AUROC, 0.75; CI, 0.65–0.84), SBP (AUROC, 0.63; CI, 0.54–0.74), and SI (AUROC, 0.64; CI, 0.54–0.75) were predictive of MT in normotensive patients. ETCO2 cutoff for MT was 26 mm Hg. The positive predictive value was 16.1%, and negative predictive value was high at 98.1%. CONCLUSION: Prehospital ETCO2 is predictive of mortality and MT. ETCO2 outperformed traditional measures such as SBP and SI in the prediction of mortality. ETCO2 may outperform traditional measures in predicting need for transfusion in occult shock. LEVEL OF EVIDENCE: Diagnostic test, level III.